TEKNOLOGI PENANGGULANGAN DAN PENGENDALIAN KERUSAKAN LINGKUNGAN PESISIR, PANTAI DAN LAUT UNTUK MENDUKUNG PENGEMBANGAN PARIWISATA - Suwedi, Nawa (Jurnal Teknologi Lingkungan, 2006)
Erosion, sedimentation, sea level rise, tsunami, sea water pollution, coralreef and mangrove forest destruction are problems, that have to beconsidered during planning, development and management of the coastal,sea and marine tourism activity. Alternative technology such as naturaland man made coastal and sea protections (revetment, bulkhead, seawall, jetty, groin, breakwater, submerged artificial reef, oil boom, oilskimmer) and information technology can be used and applied for thispurpose.